1996
DOI: 10.1007/bf00114627
|View full text |Cite
|
Sign up to set email alerts
|

Complete degradation of xenobiotic surfactants by consortia of aerobic microorganisms

Abstract: Linear alkylbenzene sulphonates are primarily attacked via a hydroxylation of the alkyl chain from the methyl group followed by beta-oxidation. The alkyl chain is metabolized by pure cultures to give sulphophenyl carboxylates which accumulate in the medium. In mixed culture, other microorganisms are capable of degrading sulphophenyl carboxylates. Formation of ethylene glycol monosulphates as major products of alkyl ethoxy sulphates demonstrates that the ether bonds are cleaved. The bacteria involved in growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
92
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 75 publications
7
92
0
5
Order By: Relevance
“…Estrogenicity can vary by a factor of 10 depending on the structure of the alkyl chain, with increased branching in the benzylic position associated with increased estrogenicity (Kim and others, 2004;Routledge and Sumpter, 1996). The biodegradability of 4-NP is reported to decrease with increasing degree of nonyl-group branching (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996). In contrast, efficient biodegradation has been reported for the linear chain isomer (4-n-NP) (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996;Bradley and others, 2008).…”
Section: -Nonylphenol (4-np)mentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogenicity can vary by a factor of 10 depending on the structure of the alkyl chain, with increased branching in the benzylic position associated with increased estrogenicity (Kim and others, 2004;Routledge and Sumpter, 1996). The biodegradability of 4-NP is reported to decrease with increasing degree of nonyl-group branching (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996). In contrast, efficient biodegradation has been reported for the linear chain isomer (4-n-NP) (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996;Bradley and others, 2008).…”
Section: -Nonylphenol (4-np)mentioning
confidence: 99%
“…The biodegradability of 4-NP is reported to decrease with increasing degree of nonyl-group branching (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996). In contrast, efficient biodegradation has been reported for the linear chain isomer (4-n-NP) (Corvini and others, 2004;Corti and others, 1995;Van Ginkel, 1996;Bradley and others, 2008).…”
Section: -Nonylphenol (4-np)mentioning
confidence: 99%
“…Kecepatan pembiakan dan pertumbuhan akan bergantung pada kultur media tempat tumbuh, pH dan suhu. Bakteri yang hidup di lingkungan perairan umumnya memiliki suhu optimum 20-45 o C dan pH 6-9,3 [9].…”
Section: Hasil Dan Pembahasanunclassified
“…Nilai BOD merupakan jumlah oksigen yang digunakan oleh bakteri untuk menguraikan hampir semua zat organik yang terlarut dan sebagian zat organik yang tersuspensi dalam air limbah [6]. Peningkatan nilai BOD terjadi karena adanya meningkatnya jumlah bahan organik sebagai sumber subtrat dan meningkatnya jumlah bakteri yang menguraikan bahan organik dalam limbah menjadi CO 2 dan H 2 O. Menurut [9] hancurnya bahan organik menjadi CO 2 dan H 2 O oleh aktivitas bakteri yang terjadi pada tahap awal akan mengakibatkan penurunan nilai oksigen terlarut, sehingga meningkatkan nilai BOD.…”
Section: Hasil Dan Pembahasanunclassified
“…Ginkel has suggested that the complete mineralization of the surfactants is accomplished by mixed cultures of microorganisms. 10) In this study, we tried to detect APPEO degrading bacteria in the topsoil of golf courses. The golf course would appear to be a place under continuous selection pressure by APPEO since APPEO-containing pesticides are sprayed to maintain the grass condition and to control the grow of weeds.…”
mentioning
confidence: 99%